Design of Desktop-Based Library Applications Using Java in Public Elementary Schools - Muhammad Encep (Universitas Djuanda, 2022)
The library is a place that provides a vast collection of books, which are financed and operated by a city or institution, and used by people who, on average, cannot afford to buy many books at their own expense. The research was carried out in a library in a Bogor City State Elementary School, which was closed. The library visitors consisted of teachers, staff, and public elementary school students. Borrowing books is usually on the instructions of teaching teachers to do school assignments concerning books that can be borrowed in the library. Library management is still done manually in processing library data, so they often experience difficulties in managing books and membership data, collecting data on the borrowing process, and returning and making reports. In addition, library operations have not yet run optimally.The research method used is Research and Development with several stages, namely Planning and Needs Analysis, Analysis by conducting Literature Studies, interviews and observations, Design, Implementation, Testing and Integration, and Maintenance. The study results are in the form of a computerized system that facilitates library activities to run well, especially in presenting fast, precise, accurate, and safe information that can overcome various existing problems.